Analisis Kualitas Pelayanan Distribusi Air Bersih PDAM Tirta Bhagasasi Cabang Rawa Tembaga Kabupaten Bekasi Tahun 2022 - Hartono Hartono; Krishantoro Krishantoro; Siti Nurbaity; Irwan Nurdiamsah (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Water is one of the most vital needs and absolutely necessary for all living things, especially humans. In everyday life, humans cannot be separated from their need for water. For this reason, the provision of clean water is very necessary for consumption purposes. The Regional Water Company, which stands for PDAM, is a regional-owned business unit, which is engaged in the distribution of clean water for the general public. PDAMs are located in every province, district, and municipality throughout Indonesia. PDAM Tirta Bhagasasi Branch Rawa Tembaga Bekasi Regency also has a fairly wide service area and customers are increasing every year, with this PDAM Tirta Bhagasasi Rawa Tembaga is required to always be responsive to the wants and needs for clean water that meets community standards, but in reality there are still many customers who complain about water distribution services. The purpose of this study was to determine and analyze the quality of clean water services using Zeithaml theory. The method used is a qualitative approach with a descriptive type of research. The results of this study based on an analysis of the quality of services provided in terms of facilities and infrastructure are good, with a large parking area and a clean customer counter area that makes transactions, communication communicates then the services provided are currently good in accordance with the lack of customer complaints in addition to making it easier Consumers of PDAM Tirta Bhagasasi Rawa Tembaga Branch also provide Customer Hotlines and information through social media ranging from Twitter, Instagram and Facebook, in providing services there is a technology-based excellent service application or PP/BTI to facilitate service and have a very good impact in resolving customer complaints of PDAM Tirta Bhagasasi Rawa Tembaga Branch.